EPSIN1 Modulates the Plasma Membrane Abundance of FLAGELLIN SENSING2 for Effective Immune Responses . Issue 4 (24th February 2020) - Collins, Carina A.; LaMontagne, Erica D.; Anderson, Jeffrey C.; Ekanayake, Gayani; Clarke, Alexander S.; Bond, Lauren N.; Salamango, Daniel J.; Cornish, Peter V.; Peck, Scott C.; Heese, Antje
Abstract : Loss of a trans-Golgi network clathrin adaptor impairs immunity to Pseudomonas bacteria and defense signaling, correlating with lower receptor kinase and coreceptor levels in the plasma membrane. Abstract: The plasma membrane (PM) provides a critical interface between plant cells and their environment to control cellular responses. To perceive the bacterial flagellin peptide flg22 for effective defense signaling, the immune receptor FLAGELLIN SENSING2 (FLS2) needs to be at its site of function, the PM, in the correct abundance. However, the intracellular machinery that controls PM accumulation of FLS2 remains largely undefined. The Arabidopsis ( Arabidopsis thaliana ) clathrin adaptor EPSIN1 (EPS1) is implicated in clathrin-coated vesicle formation at the trans-Golgi network (TGN), likely aiding the transport of cargo proteins from the TGN for proper location; but EPS1's impact on physiological responses remains elusive. Here, we identify EPS1 as a positive regulator of flg22 signaling and pattern-triggered immunity against Pseudomonas syringae pv tomato DC3000. We provide evidence that EPS1 contributes to modulating the PM abundance of defense proteins for effective immune signaling because in eps1, impaired flg22 signaling correlated with reduced PM accumulation of FLS2 and its coreceptor BRASSINOSTEROID INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1 (BAK1). The eps1 mutant also exhibited reduced responses to the pathogen/damage-associated molecular patterns elf26 and AtPep1, which are perceived by the coreceptor BAK1 and cognate PM receptors. Furthermore, quantitative proteomics of enriched PM fractions revealed that EPS1 was required for proper PM abundance of a discrete subset of proteins with different cellular functions. In conclusion, our study expands the limited understanding of the physiological roles of EPSIN family members in plants and provides novel insight into the TGN-associated clathrin-coated vesicle trafficking machinery that impacts plant PM-derived defense processes.